2021
DOI: 10.1126/scitranslmed.abg2112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Pf77 and male development gene 1 as vaccine antigens that induce potent transmission-reducing antibodies

Abstract: Malaria vaccines that disrupt the Plasmodium life cycle in mosquitoes and reduce parasite transmission in endemic areas are termed transmission-blocking vaccines (TBVs). Despite decades of research, there are only a few Plasmodium falciparum antigens that indisputably and reproducibly demonstrate transmission-blocking immunity. So far, only two TBV candidates have advanced to phase 1/2 clinical testing with limited success. By applying an unbiased transcriptomics-based approach, we have identified Pf77 and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Both Pf 77 and Pf MDV-1 display less antigenic polymorphism and are known to induce naturally occurring antibodies in individuals living in endemic areas of Africa. These antigens are highly immunogenic and can induce transmission-reducing antibodies which may aid in the reduction of oocyst counts in Anopheles mosquito midgut ( 153 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%
“…Both Pf 77 and Pf MDV-1 display less antigenic polymorphism and are known to induce naturally occurring antibodies in individuals living in endemic areas of Africa. These antigens are highly immunogenic and can induce transmission-reducing antibodies which may aid in the reduction of oocyst counts in Anopheles mosquito midgut ( 153 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%
“…MDV1 play a critical role in female gametocyte activation and accumulates in a few foci in the activated male gametocyte which are maintained until exflagellation. Additionally, Pf MDV1 generates naturally occurring antibodies in the adult population of Ghana, hinting that targeting these antigens could result in long-lasting immune responses (Tripathi et al 2021 ). Recently, researchers identified a new protein called microgamete surface protein (MiGS) which is expressed in both the sex gametocytes of P. falciparum but is upregulated specifically in male gametocytes.…”
Section: Genes Associated With Gametocyte Activationmentioning
confidence: 99%
“…Antibodies against specific epitopes of these antigens reduced transmission of P. falciparum parasites ( 10 14 ), supporting further investigation of these antigens as potential TBVs ( 15 ). Initiatives to identify ( 16 ) and characterize ( 17 , 18 ) novel TBV candidates have been stimulated by the availability of sexual stage specific transcriptome ( 19 ) and proteome datasets ( 20 , 21 ). These studies demonstrated that antigens enolase ( 17 ), Pf77 and PfMDV1 ( 18 ) induce antibodies with transmission reducing activity (TRA) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Initiatives to identify ( 16 ) and characterize ( 17 , 18 ) novel TBV candidates have been stimulated by the availability of sexual stage specific transcriptome ( 19 ) and proteome datasets ( 20 , 21 ). These studies demonstrated that antigens enolase ( 17 ), Pf77 and PfMDV1 ( 18 ) induce antibodies with transmission reducing activity (TRA) in mice. However, future studies are needed to determine whether the observed efficacy is reproducible and should include the optimization of protein expression and vaccine formulations.…”
Section: Introductionmentioning
confidence: 99%